Sterol Constituents of Sea Fan (Gorgonia mariae) as Potential Candidates of MPro Protein SARS-CoV-2 Inhibitor: in silico Study - Kelutur, Faruk Jayanto (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Ethnobotanically, sea fan was a group of gorgonian coral that have used the Maluku people as medicinal ingredients with secondary metabolites containing sterols, terpenoids, and alkaloids that have anti-inflammatory, anti-viral, anti-cancer, analgesic, gastroprotective, anti-bacterial, anti-cancer, and anti-fouling agents. However, the effectiveness of sterols as anti-viral SARS-CoV-2 has not been reported, so research was needed. The initial stage of targeting (SwissTargetPrediction), binding affinity (Autodock Tools 4.2), and amino acid interactions (Discovery Studio 2016 Client®). The route of administration, pharmacokinetic properties, and acute oral toxicity (LD50) were predicted by Lipinski's rule of five, pre-ADMET, and ProTox-II. The results of target class obtained probability of 10.6% (4,24-dimethyl cholesta-7,22-dien-3ß-ol and 4,24-dimethyl-22-dehydro-cholestanol) and 11, 8% (dinosterol). Binding affinity (ΔG, kcal/mol and Ki, nM) potentially 4,24-dimethyl cholesta-7,22-dien-3ß-ol (-9.90; 55.13) > dinosterol (-9.77; 68.66) > 4,24-dimethyl-22-dehydro-cholestanol (-9.48; 113.33), respectively with the crucial amino acid, Asp187. The test compound has a log P value > 5, so solubility must be considered. Pre-ADMET showed an excellent disposition as a drug and was not mutagenic and carcinogenic. However, the distribution of plasma proteins and the dose of LD50 need to be considered. Thus, sea fan sterols have potential as MPro protein inhibitors.